On the Mechanism of Catalytic Decarboxylation of Carboxylic Acids on Carbon-Supported Palladium Hydride - Deng, Fuli; Huang, Juanjuan; Ember, Erika E.; Achterhold, Klaus; Dierolf, Martin; Jentys, Andreas; Liu, Yue; Pfeiffer, Franz; Lercher, Johannes A. (ACS Catalysis, 2021)
The high chemical stability of aliphatic carboxylic acid makes catalytic decarboxylation at low temperatures challenging. We show that arylaliphatic acids (Ar-CnH2n-COOH, n ≥ 1) decarboxylate on carbon-supported Pd nanoparticles (Pd/C) at 90 °C with 100% selectivity. In situ XANES during decarboxylation of preadsorbed substrates indicates that the active phase is α-phase palladium hydride (α-PdHx). The reaction rate is enhanced by one order of magnitude when hydrogen is preadsorbed. Tracing deuterium labeling positions, it is concluded that carboxylic acid (Ar-CnH2n-COOH) undergoes an α-C-H bond dissociation on the Pd surface to the Ar-(CH2)n-1-CH*-COO∗ intermediate in the first step, followed by the C-COO scission, and finally, Ar-(CH2)n-1-CH∗ reacts with two sorbed H to produce Ar-(CH2)n-1-CH3. The high rates are related to the concentration of hydride present on the catalyst particles to complete the catalytic cycle in a Mars-van Krevelen-type mechanism and the rate of H/D exchange at the α-C-H position.
CRIS-Team Scopus Importer:2023-03-08
Keywords: arylaliphatic carboxylic acid; decarboxylation; mechanism; palladium hydride; Pd/C catalyst